How far is too far? An analysis of students’ perceptions of the impact of distance between university and family home on academic performance - Costa, Rosalina (2018)
Transition to university is a challenging phase in youngsters’ lives. The literature indicates that geographical distance separating the places of study and of family residence adds to the difficulties of transition and adjustment to university. Recent evidence suggests that it also negatively impacts students’ grades. Despite important work done by economists, geographers and psychologists, sociology has devoted scarce interest in understanding this topic. This article seeks to bridge this gap, specifically exploring the reasons justifying the largely ignored effect of distance between the university and family home in academic performance. The study draws on data on undergraduate students of a Portuguese public university, collected through an online survey. Two dimensions, one more related to practical life occupations and another more linked to personal feelings and activities, are examined. It is argued that the negative impact of distance is mainly due to homesickness and to the time spent traveling home. Results from such analysis are twofold socially relevant: of the utmost importance for families, academics and students' support services, deserve to be seriously considered by policy makers deciding on the territorial distribution of higher-education institutions.